Library-Faculty Referencing and Plagiarism Pilot Using Technology-Mediated Feedback for Change. Issue 4 (1st October 2020) - O'Donnell, Rosemary; Maloney, Kayla; Masters, Kate; Liu, Danny
ABSTRACT: The University of Sydney Library piloted an initiative in 2017 that used feedback and learning analytics to address referencing errors in undergraduate student assignments. We collaborated with teaching staff to deliver standardised feedback and learning materials to students, combining several educational technologies in use at the University. We discuss our pilot through three lenses: technology, collaboration and evaluating impact. Key findings include that technology affords opportunities for student support however integration issues can complicate the streamlining of workflows. Moreover, it is not possible for non-embedded library staff to align technologies with pedagogy and learning outcomes. Collaborations between library and teaching staff include a shared understanding of the value of referencing as an ethical practice. Teaching staff, however, may be unable to deliver referencing feedback in a way that is consistent with an externally designed initiative. When evaluating the impact of our pilot we found that students often display a lack of understanding about the role of feedback in their learning. Recommendations include that teaching staff should drive the use of technologies within their units of study, and that instructionally designed feedback planning is key in delivering consistent feedback, developing student feedback literacy and in supporting referencing as ethical practice.